THE CHARACTERISTICS AND COMPLEXITY OF TRANSLATING TERMS IN THE SPHERE OF DESIGN AND FASHION - Ochilova Ugiloy Turaevna (Western European Studies, 2024)
The article sheds light on the complexities of translating language in the design and fashion sphere. Furthermore, it emphasizes the issues provided by specialist vocabulary, cultural subtleties, and the fast growth of trend-driven language. It also investigates how historical and cultural settings influence the meaning and adaption of terminology, highlighting the need of cultural sensitivity. Furthermore, it tackles the multidisciplinary aspect of the topic, which necessitates understanding of art and technology. The article emphasizes the need of translators balancing linguistic correctness, creative interpretation, and audience adaptability in order to maintain the authenticity and attractiveness of fashion terminology in other languages and cultures
Keywords: design; fashion; terms; terminology